Facet dependence of leakage current and carrier concentration in m‐plane GaN Schottky barrier diode fabricated with MOVPE (Phys. Status Solidi A 8∕2017). Issue 8 (14th August 2017) - Tanaka, Atsushi; Barry, Ousmane1; Nagamatsu, Kentaro; Matsushita, Junya; Deki, Manato; Ando, Yuto; Kushimoto, Maki; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract : The background of this cover page shows a superimposed emission microscope image observed from backside of a GaN m ‐plane Schottky barrier diode with reverse biased condition. It can be observed that the epitaxial layer of m ‐plane GaN has pyramidal hillocks at the surface, and only facets inclined toward the [0001] direction (+ c facet) have emission due to leakage current. Three images at the corner are differential interference contrast microscopy image (upper left), photoluminescence intensity mapping image (PL, upper right), and cathode luminescence image (CL, lower left), respectively, observing the same pyramidal hillocks to investigate the characteristics of each facet. The PL image indicates the intensity of near‐band‐edge emission (around 363 nm wavelength) of the facets. Details are discussed in the article by Tanaka et al. (no.1600829 ). The + c facets have high emission intensity, indicating that there is a high impurity concentration in the + c facets. Furthermore, we consider this is the reason that + c facets have high leakage current. The CL image is a panchromatic image, and facets inclined toward [000‐1] direction (− c facet) have lowest emission. Together with PL intensity mapping it can be considered that − c facets have less yellow emission and less impurity concentration.